Holistic Medicine III: The Holistic Process Theory of Healing - Søren Ventegodt; Niels Jørgen Andersen; Joav Merrick (The Scientific World Journal)
It is possible to understand the process of healing from a holistic perspective. According to the life mission theory, we can stretch our existence and lower our quality of life when we are in crises, to survive and adapt, and we can relax to increase our quality of life when we later have resources for healing. The holistic process theory explains how this healing comes about: Healing happens in a state of consciousness exactly opposite to the state of crises. The patient enters the “holistic state of healing” when the (1) patient and (2) the physician have a perspective in accordance with life, (3) a safe environment, (4) personal resources, (5) the patient has the will to live, (6) the patient and (7) the physician have the intention of healing, (8) the trust of the patient in the physician, and (9) sufficient holding. The holding must be fivefold, giving the patient (1) acknowledgment, (2) awareness, (3) respect, (4) care, and (5) acceptance. The holistic process has three obligatory steps: (1) to feel, (2) to understand, and (3) to let go of negative decisions. This paper presents a theory for the holistic process of healing, and lists the necessities for holistic therapy restoring the quality of life, health, and ability to function of the patient.